Perancangan Mesin Penyangrai Kopi Tipe Rotari Berbasis Mikrokontroler Arduino - Aidil zamri (Jurnal Teknik Mesin, 2023)
Coffee is one of Indonesia's leading export commodities in the agricultural sector. Good coffee quality makes Indonesia one of the largest coffee exporting countries in the world. The process of making coffee involves many stages or processes, from harvesting to producing coffee grounds. One of the important stages in coffee production is the process of roasting the coffee beans. This study aims to design a rotary type coffee roaster based on Arduino Microcontroller. The working principle of this machine is to control the temperature and rotation of the roasting cylinder using the Arduino Uno as the controller for the temperature sensor and motor. The method used in this study is the design method, namely the design calculations are carried out on the supporting elements of the coffee roaster machine. From the design, the engine specifications are obtained with a cylinder size of 500 mm long, 130 mm radius, maximum rotation of 80 Rpm, 1HP electric motor and 28 mm shaft size.